Kinetics of pneumococcal antibodies among HIV-exposed, uninfected infants in Botswana. Issue 33 (5th August 2022) - Uffman, Emilie A.; Li, Shuk Hang; Chen, Jui-Lin; Allen, Noel; Boiditswe, Sefelani; Fouda, Genevieve G.; Hurst, Jillian H.; Patel, Mohamed Z.; Steenhoff, Andrew P.; Cunningham, Coleen K.; Qin, Emily; Davenport, Clemontina A.; et al.
Highlights: HEU and HUU infants develop protective antibodies to PCV-13 given in a 3 + 0 schedule. Levels of pneumococcal IgG subclass antibodies were similar in HEU and HUU infants. Pneumococcal antibodies following PCV-13 waned substantially by 12 months of age. Abstract: Background: Streptococcus pneumoniae is a leading cause of severe infections among children. Despite vaccination, HIV-exposed, uninfected (HEU) children have a higher incidence of invasive pneumococcal disease than HIV-unexposed, uninfected (HUU) children. We sought to compare the immunogenicity of 13-valent pneumococcal conjugate vaccine (PCV-13) in HEU and HUU infants. Methods: We conducted a prospective cohort study of 134 mother-infant dyads in Botswana. Infants received PCV-13 doses at 2, 3, and 4 months through routine clinical care. We measured IgG antibodies specific to vaccine serotypes in sera collected from infants at 0, 5, and 12 months of age. We calculated the proportion of infants with protective IgG levels (≥0.35 µg/mL) to specific pneumococcal serotypes. Results: At birth, fewer than half of infants had protective IgG levels to serotypes 1 (38%), 3 (46%), 4 (33%), 5 (23%), 6B (40%), 7F (44%), 9 V (44%), and 23F (46%). Compared to HUU infants (n = 97), HEU infants (n = 37) had lower antibody concentrations at birth to serotypes 5 (p = 0.046) and 19A (p = 0.008) after adjustment for maternal age and infant birth weight. More than 80% of HEU and HUU infants developed protective antibody levels to each of the 13 vaccine serotypes following PCV-13 vaccination. Median concentrations of antibodies to pneumococcal serotypes declined by 55–93% between 5 and 12 months of age, with fewer than half of infants having protective antibody levels to serotypes 1 (47%), 3 (28%), 9 V (44%), 18C (24%), and 23F (49%) at 12 months of age. Conclusions: Both HEU and HUU infants developed protective antibody responses to PCV-13 administered in a 3 + 0 schedule. However, antibody concentrations to many pneumococcal serotypes waned substantially by 12 months of age, suggesting that a PCV-13 booster dose in the second year of life may be needed to maintain protective pneumococcal antibody levels in older infants and young children.